2023
DOI: 10.3390/batteries9070356
|View full text |Cite
|
Sign up to set email alerts
|

Iron-Decorated Nitrogen/Boron co-Doped Reduced Graphene Oxide Aerogel for Neutral Rechargeable Zn-Air Batteries

Yuyun Irmawati,
Falihah Balqis,
Pilar Bela Persada
et al.

Abstract: Zn-air batteries (ZABs) with neutral electrolytes offer a significantly longer lifespan and better recyclability than alkaline ones. However, low-performance bifunctional catalytic activities for oxygen reduction or evolution reaction (i.e., ORR/OER) in neutral electrolytes still hamper their development. Here, we report iron nanoparticle-decorated nitrogen/boron co-doped reduced graphene oxide aerogel (Fe-NBrGO) with distinguished ORR/OER activity, enabling its application in neutral rechargeable ZABs. Taking… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 77 publications
0
2
0
Order By: Relevance
“…The insertion of N/B moieties can create active sites for transition metals that can exhibit high ORR in the whole system. Y. Irmawati et al 117 reported a typically designed nanocomposite of iron-decorated N/B co-doped reduced graphene oxide (rGO-NB/Fe) as an electro-catalyst for ORR and OER systems, acting as alkaline and neutral electrolytes, respectively and creating active sites that can modify the electronic structure of rGO in the system. Thus, its applicability (3D porous structure) as graphene aerogels with N/B moieties, with Fe-decorated nanocomposite, for a highly stable Zn–Air battery (34 mW cm −2 in power density and remaining stable for 284 h; ∼852 cycles) was acclaimed.…”
Section: Substitutional Doping Of Graphene and Its Significancementioning
confidence: 99%
“…The insertion of N/B moieties can create active sites for transition metals that can exhibit high ORR in the whole system. Y. Irmawati et al 117 reported a typically designed nanocomposite of iron-decorated N/B co-doped reduced graphene oxide (rGO-NB/Fe) as an electro-catalyst for ORR and OER systems, acting as alkaline and neutral electrolytes, respectively and creating active sites that can modify the electronic structure of rGO in the system. Thus, its applicability (3D porous structure) as graphene aerogels with N/B moieties, with Fe-decorated nanocomposite, for a highly stable Zn–Air battery (34 mW cm −2 in power density and remaining stable for 284 h; ∼852 cycles) was acclaimed.…”
Section: Substitutional Doping Of Graphene and Its Significancementioning
confidence: 99%
“…Nonprecious transition metal–nitrogen–carbon materials have been well-explored as promising candidates for ORR/OER/HER catalysts. 9–12 Among the nonprecious transition metals, Co-based catalysts are stated to be near the peak of OER/HER volcano plots, indicating their highly efficient and competitive OER/HER activity. 13,14 Meanwhile, although Fe-based catalysts exhibit relatively low OER/HER activities, they are considered to be some of the best substitutes for Pt-based catalysts owing to their high ORR activity.…”
Section: Introductionmentioning
confidence: 99%